Tautology Proof – How to Prove (p -> q) ? (q -> r) -> (p -> r) Without Truth Table

boolean-algebradiscrete mathematicslogicpropositional-calculus

I am looking for a way to prove that the statement, $[(p \to q) \land (q \to r)] \to (p \to r)$, is a tautology without the help of the truth table. By using only Laws and Theorems like De Morgan's Law, Domination Law, etc. Also, I can't use the rules of inference. Please help, thank you.

Best Answer

As correctly suggested by Wuestenfux, first you should decompose $\to$. Then, you should apply several logical equivalences to simplify your formula to $\top$ (a formula that is always true). A complete simplification of your formula, using the logical equivalences listed here, is the following:

\begin{align} &\big((p \to q) \land (q \to r) \big) \to (p \to r) \\ \equiv \ & \lnot \big( (\lnot p \lor q) \land (\lnot q \lor r) \big) \lor (\lnot p \lor r) &\text{decomposition of }\to \\ \equiv \ & \lnot (\lnot p \lor q) \lor \lnot (\lnot q \lor r) \lor \lnot p \lor r&\text{De Morgan} \\ \equiv \ & (\lnot\lnot p \land \lnot q) \lor (\lnot\lnot q \land \lnot r) \lor \lnot p \lor r &\text{De Morgan} \\ \equiv \ & \lnot p \lor (\lnot\lnot p \land \lnot q) \lor (\lnot\lnot q \land \lnot r) \lor r &\text{commutativity} \\ \equiv \ & \big((\lnot p \lor \lnot\lnot p) \land (\lnot p \lor \lnot q)\big) \lor \big((\lnot\lnot q \lor r) \land (\lnot r \lor r) \big) &\text{distributivity} \\ \equiv \ & \big(\top \land (\lnot p \lor \lnot q)\big) \lor \big((\lnot\lnot q \lor r) \land \top \big) &\text{negation law} \\ \equiv \ & (\lnot p \lor \lnot q) \lor (\lnot\lnot q \lor r) &\text{identity law} \\ \equiv \ & \lnot p \lor (\lnot q \lor \lnot\lnot q) \lor r &\text{associativity} \\ \equiv \ & \lnot p \lor \top \lor r &\text{negation law} \\ \equiv \ & \top &\text{domination law} \\ \end{align}

Related Question